Antibacterial nano coating and its preparation method and application
By adding modified resin and modified nano rice husk powder to the antibacterial nanocoatings, the problems of insufficient mechanical and mechanical properties, waterproof properties and brightness of existing antibacterial coatings have been solved, achieving wider applications and better market prospects.
Patent Information
- Application Number
- CN202410918072.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-09
AI Technical Summary
The existing antibacterial nanocoatings have problems such as poor mechanical and mechanical properties, poor waterproof properties and low brightness.
By adding modified resin and modified nanorice husk powder to the antibacterial nanocoating, the modified resin is used to improve brightness and waterproof performance, and the modified nanorice husk powder is used to enhance antibacterial effect and mechanical and mechanical properties.
It has achieved the realization that while maintaining excellent antibacterial properties, it has greatly improved the waterproofness, mechanical and brightness of the paint, expanding the application field and market prospects of antibacterial coatings.
Smart Images

Figure BDA0004936520820000141 
Figure BDA0004936520820000151
Abstract
Description
Technical Field
[0001] The present invention relates to the field of antibacterial coatings, and in particular to an antibacterial nano coating and a preparation method and application thereof. Background Art
[0002] Paint is one of the indispensable materials for the development of the national economy. It is a material that can be well bonded with the base material and form a complete and tough protective film when applied to the surface of an object. Due to the many special functions of paint, there are many varieties of paint. In recent years, with the improvement of people's work and living standards, the requirements for work and living environment are also constantly increasing. Among them, antibacterial paint is one of the environmental products born out of this demand.
[0003] Antimicrobial coatings are special functional materials designed to improve hygiene levels and prevent biological contamination on the surface of materials by inhibiting or killing surface microorganisms (including bacteria, fungi, viruses, etc.). Its background technology covers multiple fields such as materials science, chemistry, and microbiology, and is designed to meet the growing demand for antimicrobial properties in different industries such as medical care, food processing, home decoration, and public facilities. Traditional antimicrobial coatings usually rely on the addition of antimicrobial agents, which can be divided into natural antimicrobial agents (such as plant extracts), organic antimicrobial agents (such as organic halides, quaternary ammonium salts, etc.) and inorganic antimicrobial agents (such as compounds of silver, copper, and zinc, especially silver-loaded antimicrobial agents).
[0004] Early antibacterial coatings mainly focused on the application of inorganic antibacterial agents, because they exhibit good stability and durability, are not easily invalidated by changes in the external environment, and have relatively low toxicity to the human body. With the development of nanotechnology, nanomaterials have begun to be widely used in antibacterial coatings, significantly improving the antibacterial efficacy of coatings. For example, nanosilver has become a popular choice due to its broad-spectrum and efficient antibacterial properties. Through nano-processing, the surface area of silver particles is greatly increased, which enhances the chance of contact with microorganisms, thereby improving the antibacterial efficiency. In addition, the introduction of photocatalyst technology, such as nano-titanium dioxide, can activate the production of free radicals under light, effectively decompose microorganisms, and realize an environmentally friendly antibacterial solution. However, existing antibacterial nano-coatings generally have technical problems such as poor mechanical properties, poor waterproof performance, and low brightness.
[0005] Therefore, in order to solve the above problems, the present invention provides an antibacterial nano coating and a preparation method thereof. The antibacterial nano coating prepared by the present invention can ensure that it has excellent antibacterial and environmental protection properties while greatly improving its waterproofness, mechanical properties and high brightness properties, has comprehensive coating application functions, greatly expands the application field and environment of antibacterial coatings, and has very excellent market prospects. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present invention provides an antibacterial nano-coating, the raw materials, measured by mass, include: 40 to 60 parts of water-based resin, 10 to 20 parts of modified resin, 2 to 5 parts of modified nano rice husk powder, 5 to 10 parts of filler particles, 1 to 5 parts of functional additives, and 40 to 80 parts of deionized water.
[0007] As a preferred solution, the water-based resin is a composition of a water-based acrylic resin and a water-based amino resin.
[0008] As a preferred solution, the mass ratio of the water-based acrylic resin to the water-based amino resin is (4-6): (0.5-1.5).
[0009] As a preferred solution, the mass ratio of the water-based acrylic resin to the water-based amino resin is (4.5-5):(0.8-1).
[0010] As a preferred solution, the mass ratio of the water-based acrylic resin to the water-based amino resin is 4.5:1.
[0011] As a preferred solution, the modified resin is an epoxy-modified composite resin.
[0012] As a preferred solution, the preparation method of the epoxy-modified composite resin comprises the following steps: S1: methyl methacrylate is mixed with butyl acrylate, dicyclopentenyl acrylate, part of the initiator, the auxiliary agent, the dispersant and the solvent, and stirred evenly, and the temperature is raised to 65-70°C, and the reaction is stirred for 3-5 hours; S2: after the reaction is completed, the acrylic acid-modified epoxy resin and the remaining initiator are added, the temperature is lowered to 55-60°C, the reaction is stirred for 5-5.5 hours, and the reaction is neutralized and emulsified after completion.
[0013] As a preferred solution, the mass ratio of methyl methacrylate, butyl acrylate, dicyclopentenyl acrylate and acrylic acid-modified epoxy resin is (12-14): (5-6): (0.1-0.3): (1.5-2).
[0014] As a preferred solution, the mass ratio of methyl methacrylate, butyl acrylate, dicyclopentenyl acrylate and acrylic acid-modified epoxy resin is 12.5:5.5:0.2:1.8.
[0015] As a preferred solution, the initiator is any one of ammonium persulfate, sodium persulfate and potassium persulfate.
[0016] As a preferred solution, the initiator is ammonium persulfate.
[0017] As a preferred solution, the auxiliary agent is diethanolamine and / or triethanolamine.
[0018] As a preferred solution, the auxiliary agent is diethanolamine.
[0019] As a preferred solution, the dispersant is at least one of fatty alcohol polyoxyethylene ether and aromatic phenol polyoxyethylene ether.
[0020] As a preferred solution, the dispersant is aromatic phenol polyoxyethylene ether, specifically phenethyl phenol polyoxyethylene ether.
[0021] As a preferred solution, the solvent is a mixed solvent of deionized water and acetone.
[0022] As a preferred solution, the mass ratio of the deionized water to acetone is (4-5):(1-2).
[0023] As a preferred solution, the mass ratio of the deionized water to acetone is 4.5:1.
[0024] As a preferred solution, the viscosity of the acrylic modified epoxy resin is 400-1000 mPa·s.
[0025] As a preferred solution, the viscosity of the acrylic modified epoxy resin is 600-900 mPa·s.
[0026] As a preferred solution, the preparation method of the modified nano rice husk powder includes the following steps: S1: adding a dispersant into deionized water and stirring thoroughly, then adding nano rice husk powder, nano silver powder, organic acid anhydride and silane coupling agent in sequence while stirring, and heating to 50-65° C. after the addition is completed to obtain a mixed solution; S2: dispersing the mixed solution at a high speed of 6000-10000 r / min for 15-20 minutes, adding it to a circulating nano grinder for cyclic grinding until composite particles of the desired particle size are obtained, and taking them out.
[0027] As a preferred solution, the dispersant is any one of BYK particle dispersants.
[0028] As a preferred solution, the average particle size of the nano rice husk powder is 80 to 200 nm.
[0029] As a preferred solution, the average particle size of the nano silver powder is 10 to 30 nm.
[0030] As a preferred solution, the average particle size of the modified nano rice husk powder is 40 to 50 nm.
[0031] As a preferred solution, the mass ratio of the nano rice husk powder, nano silver powder, organic acid anhydride and silane coupling agent is (25-30): (1-1.5): (3-5): (0.5-2).
[0032] As a preferred solution, the organic acid anhydride is any one of succinic anhydride and maleic anhydride.
[0033] As a preferred solution, the silane coupling agent is 3-aminopropyltriethoxysilane.
[0034] In the present invention, by adding the modified nano rice husk powder prepared as above, the group functionalization on the surface of the rice husk powder can be effectively promoted, and the hydroxyl groups on the surface of the nano silver particles can be fully hydrogen bonded during the modification and grinding process of the rice husk powder, thereby greatly enhancing the attraction between the two particles. The prepared modified composite particles have strong support and connection capabilities, so that while playing an excellent antibacterial role in the use of the coating, they can also serve as excellent mechanical support points for the coating system. When external force acts, the external force can be multi-directionally dispersed through the cavitation of the particles, and through internal connection effects such as hydrogen bonds, the formed cracks can be converted back into silver streaks for propagation, thereby greatly improving the mechanical strength of the coating, especially under the action of external force and folding resistance, the continuity of the coating system can be effectively maintained.
[0035] As a preferred solution, the filler particles are at least one of zinc oxide, titanium oxide, antimony oxide, silicon dioxide, talc and bentonite.
[0036] As a preferred solution, the filler particles are at least one of zinc oxide, titanium oxide and antimony oxide.
[0037] As a preferred solution, the filler particles are zinc oxide and titanium oxide.
[0038] As a preferred solution, the mass ratio of zinc oxide to titanium oxide is (1-3): (1-3).
[0039] As a preferred solution, the mass ratio of the modified resin to the filler particles is (1.2-1.6): (0.6-1).
[0040] As a preferred solution, the mass ratio of the modified resin to the filler particles is 1.5:0.8.
[0041] The present invention can effectively improve the brightness of the coating as a whole by adding the above-mentioned modified resin, and can also further significantly enhance the surface waterproof performance of the coating system. This is mainly because, after the above-mentioned modified resin is added, its excellent inner wrapping effect can effectively strengthen the exposure degree of resin on the surface in the coating, reduce the frequency of occurrence of solid particles inside the system on the surface, and then form a flat surface composed of more resins, and on the other hand, it can also reduce the flocculation phenomenon of coating active molecules in the system, and promote the proportion of water-based resin on the surface, so as to smooth the hard surface, which is conducive to the specular reflection of light. In addition, the addition of modified resin reduces the exposure of particles on the surface, and the smooth and flat surface is not conducive to the preservation of water molecules on the surface of the coating film, so it is impossible to form a hydration layer with super hydrophilicity in a short time, and then the overall waterproof performance of the coating can be greatly improved.
[0042] As a preferred solution, the functional additive is at least one of a defoamer, a leveling agent, a wetting agent, an anti-ultraviolet absorber, a flame retardant, an antifreeze agent, a waterproofing agent, and a preservative.
[0043] As a preferred solution, the functional additives are defoaming agents and preservatives.
[0044] As a preferred solution, the mass ratio of the defoaming agent to the preservative is (0.5-1.5): (0.1-0.5).
[0045] As a preferred solution, the defoaming agent is any one of the organosilicon defoaming agents.
[0046] As a preferred solution, the preservative is at least one of isothiazolinones and benzimidazoles.
[0047] The second aspect of the present invention provides a method for preparing the above-mentioned antibacterial nano coating, and the preparation method comprises the following steps: S1: adding water-based resin, modified resin and deionized water in a container in sequence and stirring and dispersing them evenly; S2: then mixing the modified nano rice husk powder, filler particles and functional additives evenly and adding them to the container while stirring, heating to 40-45°C after the addition is completed, stirring at a speed of 200-400r / min for 30-40min, and obtaining the coating after the stirring is completed.
[0048] The third aspect of the present invention provides an application of the above-mentioned antibacterial nano-coating, including the application of the antibacterial nano-coating in the fields of medical equipment, food equipment, furniture decoration, public facilities, and architectural coatings.
[0049] The present invention has the beneficial effects:
[0050] 1. The antibacterial nano-coating provided in the present invention can ensure excellent antibacterial and environmental protection properties while greatly improving its waterproofness, mechanical properties and high brightness properties. It has comprehensive coating application functions, greatly expands the application range and environment of antibacterial coatings, and has very excellent market prospects.
[0051] 2. An antibacterial nano coating provided in the present invention can effectively promote the functionalization of the groups on the surface of rice husk powder by adding modified nano rice husk powder, and can fully hydrogen bond with the hydroxyl groups on the surface of nano silver particles during the modification and grinding process of rice husk powder, thereby greatly enhancing the attraction between the two particles. The prepared modified composite particles have strong support and connection capabilities, so that while playing an excellent antibacterial role during the use of the coating, they can also serve as excellent mechanical support points for the coating system. When external force acts, the external force can be multi-directionally dispersed through the cavitation of the particles, and through internal connection effects such as hydrogen bonds, the formed cracks can be converted back into silver streaks for propagation, thereby greatly improving the mechanical strength of the coating.
[0052] 3. The antibacterial nano coating provided in the present invention can effectively improve the brightness of the coating as a whole by adding modified resin, and can also further greatly enhance the surface waterproof performance of the coating system; after the modified resin is added, its excellent internal encapsulation effect can effectively enhance the exposure of the resin on the surface of the coating, reduce the frequency of solid particles inside the system on the surface, and thus form a flat surface composed of more resins, and on the other hand, it can also reduce the flocculation phenomenon of active molecules in the coating system, and promote the proportion of water-based resin on the surface, thereby smoothing the hard surface and facilitating the specular reflection of light. In addition, the addition of modified resin reduces the exposure of particles on the surface, and the smooth and flat surface is not conducive to the preservation of water molecules on the surface of the coating film, so it is impossible to form a super-hydrophilic hydration layer in a short time, thereby greatly improving the overall waterproof performance of the coating. DETAILED DESCRIPTION
[0053] The technical solutions in the above invention contents of the present invention will be further described and demonstrated in the form of specific implementation schemes below. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification and should not limit the scope of the claims to be protected by the present invention. All technical products based on the technical solutions described in the invention contents of the present invention should be included in the scope to be protected by the present invention.
[0054] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0055] Example 1
[0056] Embodiment 1 The first aspect provides an antibacterial nano coating, the raw materials, by mass, include: 55 parts of water-based resin, 15 parts of modified resin, 3 parts of modified nano rice husk powder, 8 parts of filler particles, 1.5 parts of functional additives, and 60 parts of deionized water.
[0057] The water-based resin is a composition of a water-based acrylic resin and a water-based amino resin, and the mass ratio of the water-based acrylic resin to the water-based amino resin is 4.5:1; the water-based acrylic resin is purchased from Aohui Paint Industry's AH-01 water-based acrylic resin product; the water-based amino resin is purchased from the American Allnex brand's Cymel P-707Resin water-based amino resin product.
[0058] The modified resin is an epoxy-modified composite resin; the preparation method of the epoxy-modified composite resin comprises the following steps, calculated by mass: S1: 12.5 parts of methyl methacrylate, 5.5 parts of butyl acrylate, 0.2 parts of dicyclopentenyl acrylate, 0.08 parts of initiator, 0.1 parts of auxiliary agent, 0.4 parts of dispersant and 30 parts of solvent are mixed and stirred evenly, heated to 65°C, and stirred for reaction for 4 hours; S2: after the reaction is completed, 1.5 parts of acrylic acid-modified epoxy resin and the remaining 0.02 parts of initiator are added, the temperature is lowered to 55°C, stirred for reaction for 5 hours, and neutralized and emulsified after completion.
[0059] The initiator is ammonium persulfate; the auxiliary agent is diethanolamine; the dispersant is phenethylphenol polyoxyethylene ether, a 601 model product purchased from Xingtai Xinlanxing Technology Co., Ltd.; the solvent is a mixed solvent of deionized water and acetone, and the mass ratio of deionized water to acetone is 4.5:1.
[0060] The average viscosity of the acrylic modified epoxy resin was 800 mPa·s, and the product was purchased from Beijing Jinhuili under the model number HD-EA604.
[0061] The preparation method of modified nano rice husk powder includes the following steps, calculated by mass: S1: adding 3 parts of BYK-161 dispersant to 300 parts of deionized water and stirring thoroughly, then adding 25 parts of nano rice husk powder, 1 part of nano silver powder, 5 parts of organic acid anhydride and 2 parts of silane coupling agent in sequence while stirring, and heating to 60°C after the addition is completed to obtain a mixed solution; S2: dispersing the mixed solution at a high speed of 8000r / min for 20min, adding it to a circulating nano grinder for cyclic grinding until composite particles with a desired particle size are obtained, and taking them out.
[0062] The average particle size of nano rice husk powder is 180nm, and the average particle size of nano silver powder is 15nm.
[0063] The average particle size of the modified nano rice husk powder is 50 nm.
[0064] The organic acid anhydride is succinic anhydride, and the silane coupling agent is 3-aminopropyltriethoxysilane.
[0065] The filler particles are zinc oxide and titanium oxide; the mass ratio of zinc oxide to titanium oxide is 2:1.
[0066] The functional additives are defoaming agent and preservative, and the mass ratio of the two is 1:0.5; the defoaming agent is purchased from the polydimethylsiloxane defoaming agent product sold by Chengdu Ningsu Additive Chemical Co., Ltd.; the preservative is methylisothiazolinone.
[0067] The second aspect of this embodiment provides a method for preparing the above-mentioned antibacterial nano coating, and the preparation method comprises the following steps: S1: adding water-based resin, modified resin and deionized water into a container in sequence and stirring and dispersing them evenly; S2: then mixing the modified nano rice husk powder, filler particles and functional additives evenly and adding them into the container while stirring, heating to 45°C after the addition is completed, stirring at a speed of 300r / min for 35min, and obtaining the coating after the stirring is completed.
[0068] Example 2
[0069] Embodiment 2 The first aspect provides an antibacterial nano coating, the raw materials are calculated by mass and include: 50 parts of water-based resin, 12 parts of modified resin, 4 parts of modified nano rice husk powder, 6 parts of filler particles, 1.5 parts of functional additives, and 60 parts of deionized water.
[0070] The water-based resin is a composition of a water-based acrylic resin and a water-based amino resin, and the mass ratio of the water-based acrylic resin to the water-based amino resin is 4:1; the water-based acrylic resin is purchased from Aohui Paint Industry's AH-01 water-based acrylic resin product; the water-based amino resin is purchased from the American Allnex brand's Cymel P-707Resin water-based amino resin product.
[0071] The modified resin is an epoxy-modified composite resin; the preparation method of the epoxy-modified composite resin comprises the following steps, calculated by mass: S1: 12.5 parts of methyl methacrylate, 5.5 parts of butyl acrylate, 0.2 parts of dicyclopentenyl acrylate, 0.08 parts of initiator, 0.1 parts of auxiliary agent, 0.4 parts of dispersant and 30 parts of solvent are mixed and stirred evenly, heated to 65°C, and stirred for reaction for 4 hours; S2: after the reaction is completed, 1.5 parts of acrylic acid-modified epoxy resin and the remaining 0.02 parts of initiator are added, the temperature is lowered to 55°C, stirred for reaction for 5 hours, and neutralized and emulsified after completion.
[0072] The initiator is ammonium persulfate; the auxiliary agent is diethanolamine; the dispersant is phenethylphenol polyoxyethylene ether, a 601 model product purchased from Xingtai Xinlanxing Technology Co., Ltd.; the solvent is a mixed solvent of deionized water and acetone, and the mass ratio of deionized water to acetone is 4.5:1.
[0073] The average viscosity of the acrylic modified epoxy resin was 800 mPa·s, and the product was purchased from Beijing Jinhuili under the model number HD-EA604.
[0074] The preparation method of modified nano rice husk powder includes the following steps, calculated by mass: S1: adding 3 parts of BYK-161 dispersant to 300 parts of deionized water and stirring thoroughly, then adding 25 parts of nano rice husk powder, 1 part of nano silver powder, 5 parts of organic acid anhydride and 2 parts of silane coupling agent in sequence while stirring, and heating to 60°C after the addition is completed to obtain a mixed solution; S2: dispersing the mixed solution at a high speed of 8000r / min for 20min, adding it to a circulating nano grinder for cyclic grinding until composite particles with a desired particle size are obtained, and taking them out.
[0075] The average particle size of nano rice husk powder is 180nm, and the average particle size of nano silver powder is 15nm.
[0076] The average particle size of the modified nano rice husk powder is 50 nm.
[0077] The organic acid anhydride is succinic anhydride, and the silane coupling agent is 3-aminopropyltriethoxysilane.
[0078] The filler particles are zinc oxide and titanium oxide; the mass ratio of zinc oxide to titanium oxide is 2:1.
[0079] The functional additives are defoaming agent and preservative, and the mass ratio of the two is 1:0.5; the defoaming agent is purchased from the polydimethylsiloxane defoaming agent product sold by Chengdu Ningsu Additive Chemical Co., Ltd.; the preservative is methylisothiazolinone.
[0080] The second aspect of this embodiment provides a method for preparing the above-mentioned antibacterial nano coating, and the preparation method comprises the following steps: S1: adding water-based resin, modified resin and deionized water into a container in sequence and stirring and dispersing them evenly; S2: then mixing the modified nano rice husk powder, filler particles and functional additives evenly and adding them into the container while stirring, heating to 45°C after the addition is completed, stirring at a speed of 300r / min for 35min, and obtaining the coating after the stirring is completed.
[0081] Comparative Example 1
[0082] The specific implementation of this comparative example is basically the same as that of Example 1, except that the antibacterial nano coating, the raw materials, by mass, include: 60 parts of water-based resin, 5 parts of modified resin, 8 parts of modified nano rice husk powder, 10 parts of filler particles, 1.5 parts of functional additives, and 60 parts of deionized water.
[0083] Comparative Example 2
[0084] The specific implementation of this comparative example is basically the same as that of Example 1, except that the water-based resin is a composition of a water-based acrylic resin and a water-based amino resin, and the mass ratio of the water-based acrylic resin to the water-based amino resin is 2:1.
[0085] Comparative Example 3
[0086] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the modified resin is an epoxy-modified composite resin; the preparation method of the epoxy-modified composite resin comprises the following steps, in parts by mass: S1: 10 parts of methyl methacrylate, 8 parts of butyl acrylate, 0.08 parts of initiator, 0.1 parts of auxiliary agent, 0.4 parts of dispersant and 30 parts of solvent are mixed and stirred evenly, the temperature is raised to 65°C, and the reaction is stirred for 4 hours; S2: after the reaction is completed, 0.5 parts of acrylic acid-modified epoxy resin and the remaining 0.02 parts of initiator are added, the temperature is lowered to 55°C, the reaction is stirred for 5 hours, and the reaction is neutralized and emulsified after completion.
[0087] Comparative Example 4
[0088] The specific implementation manner of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified nano rice husk powder comprises the following steps, measured in parts by mass: S1: adding 3 parts of BYK-161 dispersant to 300 parts of deionized water and stirring thoroughly, then adding 25 parts of nano rice husk powder, 1 part of nano silver powder, 8 parts of organic acid anhydride and 0.3 parts of silane coupling agent in sequence while stirring, and heating to 60°C after the addition is completed to obtain a mixed solution; S2: dispersing the mixed solution at a high speed of 8000r / min for 20min, adding it to a circulating nano grinder for cyclic grinding until composite particles of the desired particle size are obtained, and taking them out.
[0089] Comparative Example 5
[0090] The specific implementation manner of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified nano rice husk powder comprises the following steps, measured in parts by mass: S1: adding 3 parts of BYK-161 dispersant to 300 parts of deionized water and stirring thoroughly, then adding 25 parts of nano rice husk powder and 1 part of nano silver powder in sequence while stirring, and heating to 60° C. after the addition is completed to obtain a mixed solution; S2: dispersing the mixed solution at a high speed of 8000 r / min for 20 minutes, adding it to a circulating nano grinder for cyclic grinding until composite particles of the desired particle size are obtained, and taking them out.
[0091] Comparative Example 6
[0092] The specific implementation of this comparative example is basically the same as that of Example 1, except that the viscosity of the acrylic modified epoxy resin is 1500 mPa·s.
[0093] Comparative Example 7
[0094] The specific implementation of this comparative example is basically the same as that of Example 1, except that the modified resin is an epoxy-modified composite resin; the preparation method of the epoxy-modified composite resin comprises the following steps, in parts by mass: S1: 12.5 parts of methyl methacrylate, 5.5 parts of ethyl methacrylate, 0.2 parts of dicyclopentenyl acrylate, 0.07 parts of initiator, 0.1 parts of auxiliary agent, 0.4 parts of dispersant and 30 parts of solvent are mixed and stirred evenly, the temperature is raised to 65°C, and the reaction is stirred for 4 hours; S2: after the reaction is completed, 1.5 parts of citrate-modified epoxy resin and the remaining 0.03 parts of initiator are added, the temperature is lowered to 55°C, the reaction is stirred for 5 hours, and the reaction is neutralized and emulsified after completion.
[0095] Comparative Example 8
[0096] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of the nano rice husk powder is 500 nm, and the average particle size of the nano silver powder is 50 nm.
[0097] Performance Evaluation
[0098] Antibacterial property: The antibacterial property of the coatings prepared in the examples and comparative examples was tested with reference to the HG / T 3950-2007 standard, using data from Staphylococcus aureus and Escherichia coli after 56 days. The measured values were taken as the average of 10 tests and recorded in Table 1.
[0099] Flexural resistance: The flexural resistance of the coatings prepared in the embodiments and comparative examples was tested. After the coating was coated on the aluminum surface with a coating thickness of 2 mm, it was heated and cured, and then folded inside out at 180°C for 10 times. After that, the tape was peeled off and the area rate of the coating falling off at the crease was measured. The falling off area rate (%) = coating falling off area at the crease / total area at the crease × 100%. The measured values were taken as the average value of 10 tests and recorded in Table 2.
[0100] Surface water contact angle: The surface water contact angle test was carried out on the coatings prepared in the embodiments and comparative examples. The test droplet was 2 μL, the thickness of the coating sample was 2 mm, and the test time was 20 seconds. The surface water contact angle of the coating at this time was recorded. The measured value was the average value of 10 tests and recorded in Table 2.
[0101] Brightness: The surface brightness of the coatings prepared in the examples and comparative examples was tested. The sample coating thickness was 2 mm. A colorimeter was used for detection. The measured values were averaged over 10 tests and recorded in Table 2.
[0102] Table 1 Antibacterial test results
[0103]
[0104]
[0105] Table 2 Test results of folding resistance, surface water contact angle and brightness
[0106] Example Bending resistance (%) Water contact angle (°) Brightness (L value) Example 1 2.94 121 96 Example 2 3.24 119 95 Comparative Example 1 7.76 108 85 Comparative Example 2 4.98 110 90 Comparative Example 3 4.54 109 92 Comparative Example 4 5.08 112 91 Comparative Example 5 4.99 114 92 Comparative Example 6 3.99 111 94 Comparative Example 7 4.12 108 92 Comparative Example 8 3.86 110 93
[0107] From the data results of the embodiments and comparative examples of the present invention and Table 1 and Table 2, it can be seen that embodiments 1 and 2 using the necessary technical solution of the present invention can be significantly stronger than comparative examples 1 to 8 in terms of antibacterial properties, mechanical properties and waterproof properties. This is mainly because embodiments 1 and 2 use the correct modified resin and the addition of modified rice husk powder to ensure the antibacterial properties of the coating system while enhancing the resin exposure on the coating surface to form a stable flat surface, thereby preventing the formation of a surface hydration layer of moisture, thereby enhancing the surface waterproofness and surface brightness of the coating, overcoming the performance defects of the antibacterial coating in the prior art, and having a very excellent market prospect.
Claims
1. An antibacterial nano coating, characterized in that: The raw materials include, by weight: 40 to 60 parts of water-based resin, 10 to 20 parts of modified resin, 2 to 5 parts of modified nano rice husk powder, 5 to 10 parts of filler particles, 1 to 5 parts of functional additives, and 40 to 80 parts of deionized water; The water-based resin is a composition of a water-based acrylic resin and a water-based amino resin; The mass ratio of the water-based acrylic resin to the water-based amino resin is (4-6): (0.5-1.5); The modified resin is an epoxy modified composite resin; The preparation method of the epoxy-modified composite resin comprises the following steps: S1: methyl methacrylate, butyl acrylate, dicyclopentenyl acrylate, part of the initiator, auxiliary agent, dispersant and solvent are mixed and stirred evenly, the temperature is raised to 65-70° C., and the reaction is stirred for 3-5 hours; S2: after the reaction is completed, acrylic acid-modified epoxy resin and the remaining initiator are added, the temperature is lowered to 55-60° C., the reaction is stirred for 5-5.5 hours, and after completion, neutralization and emulsification are performed to obtain the composite resin; The mass ratio of methyl methacrylate, butyl acrylate, dicyclopentenyl acrylate and acrylic acid-modified epoxy resin is (12-14): (5-6): (0.1-0.3): (1.5-2); The initiator is any one of ammonium persulfate, sodium persulfate, and potassium persulfate; The auxiliary agent is diethanolamine and / or triethanolamine; The dispersant is at least one of fatty alcohol polyoxyethylene ether and aromatic phenol polyoxyethylene ether; The solvent is a mixed solvent of deionized water and acetone; the mass ratio of the deionized water to acetone is (4-5): (1-2); The viscosity of the acrylic modified epoxy resin is 400 to 1000 mpa·s; The preparation method of the modified nano rice husk powder comprises the following steps: S1: adding a dispersant into deionized water and stirring it completely, then sequentially adding nano rice husk powder, nano silver powder, organic anhydride and silane coupling agent while stirring, heating the mixture to 50-65° C. after the addition is completed, to obtain a mixed solution; S2: dispersing the mixed solution at a high speed of 6000-10000 r / min for 15-20 minutes, adding the mixed solution to a circulating nano grinder for cyclic grinding until composite particles with a desired particle size are obtained, and taking them out; The average particle size of the nano rice husk powder is 80 to 200 nm; the average particle size of the nano silver powder is 10 to 30 nm; The mass ratio of the nano rice husk powder, nano silver powder, organic acid anhydride and silane coupling agent is (25-30): (1-1.5): (3-5): (0.5-2); The average particle size of the modified nano rice husk powder is 40 to 50 nm; The functional additive is at least one of a defoamer, a leveling agent, a wetting agent, an anti-ultraviolet absorber, a flame retardant, an antifreeze agent, a waterproofing agent, and a preservative.
2. The antibacterial nano coating according to claim 1, characterized in that: The viscosity of the acrylic acid modified epoxy resin is 600-900 mpa·s.
3. The antibacterial nano coating according to claim 1, characterized in that: The filler particles are at least one of zinc oxide, titanium oxide, antimony oxide, silicon dioxide, talc and bentonite.
4. The antibacterial nano coating according to claim 1, characterized in that: The mass ratio of the modified resin to the filler particles is (1.2-1.6): (0.6-1).
5. A method for preparing the antibacterial nano coating according to any one of claims 1 to 4, characterized in that: Preparation method The following steps are involved: S1: adding water-based resin, modified resin and deionized water into a container in sequence and stirring and dispersing them evenly; S2: then mixing the modified nano rice husk powder, filler particles and functional additives evenly and adding them into the container while stirring, raising the temperature to 40-45°C after the addition is completed, stirring at a speed of 200-400r / min for 30-40min, and obtaining the product after the stirring is completed.
6. An application of the antibacterial nano coating according to any one of claims 1 to 4, characterized in that: This includes the application of the antibacterial nano coating in the fields of medical equipment, food equipment, furniture decoration, public facilities, and architectural coatings.
Citation Information
Patent Citations
Antibacterial nano-coating, preparation method thereof, and antibacterial nano-coating cloth
CN106085044A
Modification method of rice hull powder, modified rice hull powder and composite material
CN111647172A